The pathways of technology and class models of English language learning: reflecting the new normal era - Miftachudin; Muhammad Zulfikar (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2024)
This research aims to showcase English language learning in the new normal era from 17 May 2022 to 30 June 2023. It focuses on conditions, class models, the reasons for class model adjustment, and the role of technology. Using an open-ended questionnaire, the researchers obtained information about the phenomenon and complete data from 83 teachers in Salatiga and Semarang Regency, Central Java, Indonesia. The study findings demonstrate that the conditions of English language learning in the new normal era coped with learning adaptation, challenging learning, learning improvement, changes in character, the amusement of face-to-face classes, and low understanding of the material. Regarding class models, during two years of the pandemic, teachers predominantly used offline, blended, hybrid, and online class models. The main reasons for the adjustment in the class models were the need for social interaction, knowledge development, behavioral education, and health factors. Regarding technology’s contributions, it was crucial to develop learning materials. This study concludes with empirical insights into consideration for further development of English language learning by integrating technology and various class models so that teachers can mitigate and sustain learning due to probable extenuating circumstances in the future.